Answer:
y = - 6x - 2
Explanation:
The straight line equation is y = mx + c
First step is to bring the equation given to this form, where you make y the subject.
Now you can easily note down the gradient(m1). You will need it to find the gradient(m2) of the perpendicular line, because m1 × m2 = -1
After you have that substitute the value and the values of x and y given to find c .
Lastly, substitute the value of m2 and c into y = mx + c to find the line that is perpendicular .
Hope I was able to help:)))